Nanomaterial: a neglected bioink ingredient for 3D printing of biomineralization-enabled structural composites - Jin, Congrui; Huang, Yong; Naraghi, Mohammad; Wu, Chenglin (Frontiers in Mechanical Engineering, 2025)
In the past decades, biomineralization-enabled structural composites with self-healing and self-growing properties have attracted significant amounts of attention from the research community. In this perspective article, we recapitulate the state of the art of biomineralization-enabled structural composites, its recent advances into 3D printing, and point out that nanomaterials may possess distinctive advantages to be included in the bioink, due to their remarkable effect on mechanical reinforcement and positive influence on microbial growth and biomineralization efficiency.